Effects of Hydrilla verticillata (L.F) Royle on Phosphorus Sorption in Sediments - Wang, Lizhi; Wang, Guoxiang; Ge, Xuguang; Chen, Qiumin; Gu, Xiankun; Yu, Zhenfei (Asian Journal of Chemistry, 2011)
In order to know the effects of H. verticillata on the mechanism of phosphorus sorption, a simulated experiment was done. The effects of H. verticillata on the phosphate sorption isotherm and sorption kinetics were investigated. The results show that the concentrations of NaOH extracted phosphorous (NaOH-P), inorganic phosphorus, organic phosphorus, total phosphorus, Olsen-phosphorus, organic matter, cationic exchange capacity, Fe, Al, exchangeable Fe (Feox) and exchangeable Al (Alox) were lower of the sediments with H. verticillata than those of the control. The sediments with H. verticillata had stronger phosphorus sorption ability. H. verticillata did not significantly affect the trends of the sorption isotherms and sorption kinetics on the sediments. H. verticillata decreased both phosphate sorption efficiency and the amount of the phosphorus that can be released from sediments. The study states that H. verticillata can significantly increase the ability of phosphorus sorption is one of the mechanism of H. verticillata maintain lower phosphorus levels of the overlying water. H. verticillata can increase the ability of phosphorus sorption through affecting the contents of NaOH-P, inorganic phosphorus, organic phosphorus, Olsen-phosphorus, total phosphorus, organic matter, cationic exchange capacity, Fe, Al, Feox and Alox in sediments.